Analisis Peran Syahbandar, Kemampuan Berkomunikasi dan Ism Code Terhadap Keselamatan Pelayaran: Studi Kasus di Pelabuhan Penyeberangan Padang Bai Bali - Kurniawan Teguh Santoso; Cokorda Agung Agus Prebawa; E. Adenanthera L. D. (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
Abstract: Indonesia, which consists of thousands of islands, reaching 17,001 islands, is known as a maritime country because the ocean area is larger than the land area, around 2/3 of the total area of ​​Indonesia. Sea transportation as part of the National Transportation System needs to unite all regions of Indonesia. Maritime transportation accidents occur due to 3 (three) important factors, namely human error, technical factors and weather (natural) factors. The purpose of this research is to analyze the influence between the independent variables, namely the Role of Harbor Master, Communication Ability and ISM Code, for the dependent variable, namely Shipping Safety. The population in this study was 130 people consisting of ship crew and employees of the PT. ASDP Indonesia Ferry (Persero) Padang Bai Branch who had knowledge classification about shipping safety and the sample in this study was 100 respondents with the technique used was non-probability sampling technique namely by using quota sampling. The analytical method used is descriptive analysis and quantitative analysis, data is analyzed using multiple linear regression analysis with the help of the Statistical Package For Social Science (SPSS) software. The results of this research by testing the t-test hypothesis show that the variables Role of Harbormaster, Communication Ability and ISM Code have a positive and significant effect on shipping safety at the Padang Bai Bali Ferry Port. Based on the results of the research, it can be seen that the research model of the multiple linear regression equation is Y = 2.898 + 0.436X1 + 0.214X2 + 0.189X3 + µ. From the regression results, it can be seen that the variable that has the most dominant influence on shipping safety is the role of the harbor master variable with a regression coefficient of 0.436. With the r square test of 0.526 or 52.6%, which means that the increase in shipping safety at the Padang Bai Bali Ferry Port is influenced by the Role of the Harbor Master, Communication Ability and ISM Code, namely 52.6% and other factors that influence the increase in shipping safety at the Padang Ferry Port Bai Bali was 47.4%.